VACCINE PROPHYLAXIS AGAINST PAPILLOMAVIRUS INFECTION IN THE REPUBLIC OF KARAKALPAKSTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article presents data on the prevalence of human papillomavirus (HPV), the types that cause benign and malignant precancerous and cancerous lesions of the genitals, in particular cervical cancer. The only reliable method of preventing papillomavirus infection is vaccination. The article describes the coverage of HPV vaccination throughout the Republic of Karakalpakstan in the period 2020.